2022
DOI: 10.3389/fphar.2022.900610
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-based nanoparticles and RNA as innovative neuro-therapeutics

Abstract: RNA-delivery is a promising tool to develop therapies for difficult to treat diseases such as neurological disorders, by silencing pathological genes or expressing therapeutic proteins. However, in many cases RNA delivery requires a vesicle that could effectively protect the molecule from bio-degradation, bypass barriers i.e., the blood brain barrier, transfer it to a targeted tissue and efficiently release the RNA inside the cells. Many vesicles such as viral vectors, and polymeric nanoparticles have been men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…They consist of a cationic lipid core and a polyethylene glycol (PEG) shell, which enhance their stability and reduce their immunogenicity [ 97 ]. Several preclinical studies have shown the efficacy of lipid-based nanoparticles in delivering miRNA therapeutics to lung cancer cells [ 98 , 99 ]. For example, a recent study demonstrated that the intravenous delivery of lipid-based nanoparticles containing miR-34a mimics can inhibit lung tumor growth and metastasis in a mouse model of NSCLC [ 100 ].…”
Section: Mirna Therapeutics and Delivery Methodsmentioning
confidence: 99%
“…They consist of a cationic lipid core and a polyethylene glycol (PEG) shell, which enhance their stability and reduce their immunogenicity [ 97 ]. Several preclinical studies have shown the efficacy of lipid-based nanoparticles in delivering miRNA therapeutics to lung cancer cells [ 98 , 99 ]. For example, a recent study demonstrated that the intravenous delivery of lipid-based nanoparticles containing miR-34a mimics can inhibit lung tumor growth and metastasis in a mouse model of NSCLC [ 100 ].…”
Section: Mirna Therapeutics and Delivery Methodsmentioning
confidence: 99%
“…Much hope is put into the development of lipid-based particles [ 181 ]. The main advantage of lipid-based particles is that, as they are naturally generated and can have natural tropisms for specific organs and even particular cell types, they can achieve the goal of being specific, potent, and safe [ 181 ]. In fact, mRNA vaccines are delivered in lipid-based particles and, while they are not yet very specific, they have been proven to be safe [ 182 ].…”
Section: The Future Of Rna-based Therapies For Glioblastomamentioning
confidence: 99%
“…In fact, mRNA vaccines are delivered in lipid-based particles and, while they are not yet very specific, they have been proven to be safe [ 182 ]. Lipid-based particles can be generated artificially, which has the advantage of allowing a very homogeneous preparation, which is relatively easy to characterize, fabricate, store, and administrate [ 181 ]. Howevser, we still lack the knowledge to achieve extreme organ specificity with such types of particles.…”
Section: The Future Of Rna-based Therapies For Glioblastomamentioning
confidence: 99%
“…As intermediate tunneling, messenger ribonucleic acid (mRNA) can transport genetic codes from DNA to ribosomes for protein expression, which has emerged as a highly appealing potential to change the vaccination, protein replacement therapy, and other treatments for human diseases 1–4 . The first study of successful mRNA therapeutics in the preclinical application was published in 1990 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As intermediate tunneling, messenger ribonucleic acid (mRNA) can transport genetic codes from DNA to ribosomes for protein expression, which has emerged as a highly appealing potential to change the vaccination, protein replacement therapy, and other treatments for human diseases. 1 , 2 , 3 , 4 The first study of successful mRNA therapeutics in the preclinical application was published in 1990. 5 In addition, due to the progress of mRNA manufacturing and intercellular delivery strategy, significant development and breakthrough have been made in the mRNA‐based therapy.…”
Section: Introductionmentioning
confidence: 99%